2014
DOI: 10.21608/absb.2014.26039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metals on Some Physiological Responses in Two Fish Species Inhabiting Mediterranean Sea Coast; Damietta Governorate, Egypt.

Abstract: The present study aims to determine the concentrations of heavy metals: Cadmium, Copper, Iron, Nickel, Lead and Zinc in the two fish species, Sparus aurata and Diplodus sargus, (family: Sparidae) collected from the Mediterranean Sea Coast, Damietta Governorate, in order to: compare concentrations of metals in the different organs (gonads, kidney, liver, muscles, gills, skin and bones) and their effects on the physiological parameters (total proteins, total lipids, ASAT and ALAT) in the edible organs of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The current work showed that, the sediments contain very high levels of some heavy metals compared to water. This difference could be explained by the tendency of metals to accumulate in sediments and biomagnify along aquatic food chains The present data indicates that, the difference in the levels of bioaccumulation in different organs of fish may be due to the physiological role of edible organ with its regulatory ability and feeding behavior of the organism which play a significant role in the difference of bioaccumulation in those organs (Ghanem, 2014(Ghanem, & 2019. Data indicate that, the general increase in mean concentration of heavy metals in the samples may be due to metal bioaccumulation from water during the wet seasons.…”
Section: Concentration Of Heavy Metals In An Aquaticmentioning
confidence: 69%
“…The current work showed that, the sediments contain very high levels of some heavy metals compared to water. This difference could be explained by the tendency of metals to accumulate in sediments and biomagnify along aquatic food chains The present data indicates that, the difference in the levels of bioaccumulation in different organs of fish may be due to the physiological role of edible organ with its regulatory ability and feeding behavior of the organism which play a significant role in the difference of bioaccumulation in those organs (Ghanem, 2014(Ghanem, & 2019. Data indicate that, the general increase in mean concentration of heavy metals in the samples may be due to metal bioaccumulation from water during the wet seasons.…”
Section: Concentration Of Heavy Metals In An Aquaticmentioning
confidence: 69%
“…Proteins serve majorly in the building of cell structure and protection of the body against invaders to keep the immune system intact (Edori and Konne, 2015). The reduction of protein may be due to proteolysis and increased metabolism under toxicant stress (Remia et al, 2008;Ghanem, 2014;kola et al, 2015 andGhanem, 2019). From another angel, Das (1978) suggested that protein content goes on increasing with the advancement in the maturity of Mugil cephalus.…”
Section: Total Proteinsmentioning
confidence: 99%